ChemInform Abstract: Carbocatalyzed Oxidative C(sp2)—C(sp2) Homocouplings of Benzo‐Fused Heterocycles. Issue 14 (March 2016) - Wirtanen, Tom; Maekelae, Mikko K.; Sarfraz, Jawad; Ihalainen, Petri; Hietala, Sami; Melchionna, Michele; Helaja, Juho
Abstract: Appropriate treatment of amorphous carbon with aqua regia or concentrated nitric acid leads to oxidized carbon material which is able to catalyze homocoupling reactions of benzo‐fused heterocycles as well as β‐naphthol.